ҚАРАҚАЛПАҚ ТИЛИНДЕГИ СОРАЎ ГӘП ТҮРИНДЕГИ ФРАЗЕОЛОГИЗМЛЕР - Юсупова, Б.Т. (FAN va JAMIYAT, 2020)
The are different types of phraseologisms in the Karakalpak language according to their grammatical structure. The article is devoted to the study of phraseologisms in the form of an interrogative sentence in literary texts.